PERANAN PEREMPUAN DALAM MENINGKATKAN EKONOMI KELUARGA DI MINANGKABAU STUDI TENTANG TKW DI MALAYSIA - Najmi Najmi (Ensiklopedia of Journal, 2023)
Economic problems in the family are the most urgent problems for the lower middle class. Economic insufficiency and daily needs make people, especially women, look for other ways so that everything can be fulfilled. In Minangkabau ideally, the problem of needs in the form of food and drink should not be a thing to worry about because heirloom assets, namely people's assets in the form of rice fields and fields, should be reliable. Family and clan conflicts make the property divided by some Minangkabau people and of course it will erode itself alias exhausted. The domination of men makes some women surrender and finally choose to work outside the village to try their luck. One of the paths taken is to become a TKW because the wages offered are quite high compared to working in the country. This research will use a descriptive analysis method by using a synchronic and diachronic approach to social history. This means looking at the structure of women in Minangkabau and seeing the changes in that structure from today's point of view. In addition, it also uses the library method, namely by looking at sources such as previous studies which also discuss TKW in Indonesia. In addition, they will also use the interview method with several resource persons who have been TKW in Malaysia and what problems they encounter in the neighboring country. From the findings, it is concluded that women in Minangkabau have experienced cultural changes and in fact women living at home today are no longer. One of the causes of this is economic needs and not enough heirlooms to rely on in meeting daily needs.Keywords: Economic Problems, Minangkabau Women, TKW